Individual Difference Variables and the Occurrence and Effectiveness of Faking Behavior in Interviews - Buehl, Anne-Kathrin; Melchers, Klaus G. (Frontiers in Psychology, 2017)
There is widespread fear that applicants can fake during selection interviews and that this impairs the quality of selection decisions. Several theories assume that faking occurrence is influenced by personality and attitudes, which together influence applicants’ motivation to show faking behavior. However, for faking behavior to be effective, interviewees also need certain skills and abilities. To investigate the impact of several relevant individual difference variables on faking behavior and interview success, we conducted two studies. In Study 1, we surveyed 222 individuals to assess different personality variables, attitude toward faking, cognitive ability, self-reported faking behavior, and success in previous interviews, and in Study 2, we assessed cognitive ability, social skills, faking behavior, and interview performance in an interview simulation with 108 participants. Taken together, personality, as well as attitude toward faking, influenced who showed faking behavior in an interview, but there was no evidence for the assumed moderating effect of cognitive ability or social skills on interview success.